Meeting Report of the XIV International Small Bowel Transplant Symposium: Summary of Presentations, Workshops, and Debates From a Comprehensive Meeting on Intestinal Failure, Rehabilitation, and Transplantation, Buenos Aires, Argentina, June 10–13, 2015. Issue 2 (12th December 2017) - Gondolesi, Gabriel E.; Fernandez, Adriana; Burghardt, Karolina M.; Nowakowski, Scott; Kaufman, Stuart S.; Pascher, Andreas; Florescu, Diana; Ruiz, Phillip; Vianna, Rodrigo; Clarke, Sara; Oltean, Mihai; Rumbo, Martin; et al.
Abstract: The 2015 meeting of the Intestinal Transplant Association was held in Buenos Aires, Argentina. This was the 14th International Small Bowel Transplant Symposium, and it was the first meeting organized as a joint venture of the Transplantation Society, the Intestinal Transplant Association, and the Argentinean Transplant Society (Sociedad Argentina de Trasplantes). Innovative aspects of the classic meeting format included workshops sessions, debates, and multicenter studies. This report highlights the most prominent scientific contributions and results of the first such symposium in a Latin American country.